Anger rumination in Australia and Spain: Validation of the Anger Rumination Scale - Juan Ramos‐cejudo; José M. Salguero; Lee Kannis‐dymand; Esperanza García‐sancho; Steven Love (Australian Journal of Psychology, 2017)
Objective Rumination has been empirically supported in the experience of anger. The Anger Rumination Scale ( ARS ) was developed to assess ruminative processes in anger. The aim of this study was to evaluate the psychometric properties of the ARS in Australia and Spain. Method A large non‐clinical sample (N = 1,752) completed a battery including the ARS and measures of trait anger, anger expression and control, aggression, emotional symptoms, and emotion regulation strategies, to determine the factor structure, validity, and reliability of the ARS. Variations between the two cultural samples were also analysed. Results Confirmatory factor analysis verified the four‐factor structure of Angry Memories, Thoughts of Revenge, Angry Afterthoughts, and Understanding of Causes in both samples. Findings established good psychometric properties, evidence of convergent and discriminant validity, and associations in the expected direction with related variables. Males in both samples endorsed Thoughts of Revenge significantly higher. Spanish participants scored higher on Angry Memories and Understanding of Causes. Conclusions The ARS is a valid measure of anger rumination in Australian and Spanish populations. Further, gender and cultural variations may influence the tendency to engage in anger rumination.